THE EFFECTS OF HALAL (PERMISSIBLE) FOOD LABELING ON ISLAM CUSTOMER PURCHASE DECISION IN SOLARIA RESTAURANT MANADO - Nursanti, Windah; Tielung, Maria (Universitas Sam Ratulangi, 2014)
Emphasis on the importance of halal products is now growing. It is fast becoming a new market force and brand identifier and now moving into the mainstream market, affecting and changing perception on how business should be conducted, including from the marketing point of view. An associative research method with analytical technique is Multiple Linear Regression to examine the effects of independent variable (halal awareness, halal certification, food quality and marketing promotion) on the dependent (purchase decision).Â The data was collected through questionnaires survey that was distributed with convenience sampling method and multiple regression analysis. The sample consisted of 100 respondents from Manadonese who purchase twice in Solaria Restaurant Manado town square. The result shows halal awareness, halal certification, food quality and marketing promotion influence purchase decision simultaneously but not partially because halal awareness has no significant influence on purchase decision. This study provides insights into how customers behave in purchasing halal products. Keywords: awareness, certification, food quality